Complex of laws : interfacing different employment and patent regimes in global inventions - a piece of cake? - Lummevuo, Anne-Mari (fi=Turun yliopisto|en=University of Turku|, 2020)
This doctoral dissertation explores complexity of the international legal system related to interfacing different employment and patent regimes, from the point of view of a multinational company. The starting point for this thesis is a technology company operating in a global business wherein patents play a significant role and inventions made by employees (and subcontracted inventors) are valuable assets for the company. The relevant question in this respect is, how the international legal system affects the company when it comes to managing rights to employees’ inventions and creating a patent portfolio to protect company assets globally? One research question, explored from a comparative perspective, is valid entitlement to employee inventions. The different kinds of mechanisms for transferring the rights to inventions made by employees in the different employment regimes cause challenges in addressing the variety of country-specific differences in a company’s invention management procedures, with additional complexity resulting from third party collaboration. A specific aspect constituting valid entitlement in certain regimes is the compensation to be paid for the rights to the inventions, and how to manage disharmonized compensation systems when the inventors originate from different jurisdictions. Company’s patents need to be truly valid, for them to be capable of being utilized in value creation processes such as licensing. In order to achieve a sustainable competitive advantage, it is not sufficient for a company to merely ensure the necessary rights to inventions made by company employees. In addition, inventions also need to be secured, in this thesis using patent protection, in a valid manner. The validity explored in this thesis refers to compliance with special national security provisions, through which individual countries control, and in some cases can even prohibit, the export of certain technologies in the form of patent filings outside their national boundaries. Not complying with these provisions can affect the patent’s validity, which is not a risk any technology company wants to be taking. This thesis is particularly focused on how to deal with all of the aforementioned legal issues in the complex of laws -situations taking place in cross-border collaboration within a multinational company where an invention is the joint effort of multiple contributors originating from different jurisdictions. In respect of a single invention, the laws of the different countries regulating valid entitlement and national security simultaneously apply and need to be complied with, in order to secure valid entitlement to and global patent protection for the invention in relevant markets. This thesis addresses the company as a legal organization, needing to cope with the complexity – the legal governance. This concerns first of all the legal status of patent portfolio of a company, in terms of patent validity. However, it is also a question of company’s legal mechanisms and tools, such as contracts, and whether for example employment or subcontracting agreements sufficiently address the issue of rights to inventions made by employees or subcontracted inventors. Third dimension relates to organizational mechanisms within a company, such as policies. The analysis thus explores also issues beyond the law. This thesis provides a comprehensive overview of the legal aspects and potential pitfalls of cross-border operations of a multinational company, during the process from an invention to a patent. The case examples in this thesis provide a valuable practical insight into recognizing potential conflicts beforehand as well as examples of solutions assuring compliance. The approach is thus proactive as it attempts to identify and solve potential conflict situations beforehand, in order to avoid any future disputes. Finally, since disharmonized employment and patent regimes create complex compliance obligations for companies, the thesis explores whether it would be possible to come up with a holistic approach to comply with the differing laws, preferably by company policy or absent of that alternative, in form of future harmonization.

Tämä väitöskirja tarkastelee kansainvälisen oikeusjärjestelmän ja eri työsuhde- ja patenttilainsäädäntöjen rajapinnoilla toimimisen haasteellisuutta monikansallisen yrityksen näkökulmasta. Tutkimuksen lähtökohtana on teknologiayritys, jonka liiketoiminta on maailmanlaajuista, jossa patentit näyttelevät merkittävää roolia ja jolle työntekijöiden (ja alihankkijoiden) tekemät keksinnöt ovat arvokkaita. Tutkimus pyrkii vastaamaan kysymykseen, kuinka kansainvälinen oikeusjärjestelmä vaikuttaa yrityksen toimintaan liittyen työsuhdekeksintöoikeuksien hallinnoimiseen ja patenttiportfolion luomiseen, suojattaessa yrityksen innovaatioita globaalisti? Yksi tutkimuskysymys, vertailevasta näkökulmasta tarkasteltuna, on työsuhdekeksintöjen oikeuksien tehokkuus. Erilaiset oikeuksiensiirtomekanismit työntekijöiden tekemiin keksintöihin aiheuttavat haasteita yrityksen keksintöjen hallinnoimisen prosesseihin, joissa pitää huomioida maakohtaiset erot. Lisähaasteita tähän tuo yhteistyö kolmansien osapuolten kanssa. Yhtenä erityiskysymyksenä tarkastellaan tietyillä lainsäädäntöalueilla oikeuksiensiirron tehokkuuteen vaikuttavaa keksintökorvausta ja sitä, miten yritys hallinnoi toisistaan eroavia korvaus-järjestelmiä silloin kun keksijät ovat kotoisin eri lainsäädäntöalueilta. Yrityksen patenttien pitää olla päteviä, jotta niillä voitaisiin luoda taloudellista arvoa esim. lisensioimalla. Kestävään kilpailukykyyn ei riitä, että yritys on turvannut oikeudet työntekijöiden tekemiin keksintöihin. Keksinnöt pitää myös suojata, tässä tutkimuksessa patentein, juridisesti pätevällä tavalla. Tutkimuksessa suojauksen pätevyyttä tutkitaan erityisten kansallisten turvallisuussäännösten noudattamisen näkökulmasta. Kansallisilla turvallisuussäännöksillä yksittäiset valtiot kontrolloivat, ja joissakin tapauksissa voivat jopa kieltää, tiettyjen teknologioiden viennin maasta patenttihakemusten muodossa. Näiden säännösten noudattamatta jättäminen voi vaikuttaa patentin pätevyyteen, mitä riskiä yksikään teknologiayritys ei halua ottaa. Tutkimuksen erityisenä tarkastelukohteena on edellä mainittujen oikeudellisten kysymysten hallitseminen ”complex of laws” -tilanteissa, kansainvälisen yrityksen rajat ylittävässä yhteistyössä, jossa keksintö on usean eri lainsäädäntöalueelta lähtöisin olevan keksijän yhteisesti tekemä. Tällöin yhteen keksintöön soveltuu samanaikaisesti eri maiden oikeuksienottoa ja kansallista turvallisuutta sääteleviä lakeja, joita kaikkia yrityksen tulee noudattaa, turvatakseen keksinnön tehokkaan oikeuksienoton ja globaalisti pätevän patenttisuojauksen relevanteilla markkinoilla. Väitöskirjassa yritystä käsitellään oikeudellisena organisaationa, jonka tulee selviytyä tästä kompleksisuudesta juridisen hallinnointinsa avulla. Tämä käsittää ensinnäkin yrityksen patenttiportfolion oikeudellisen aseman, patenttien pätevyyden muodossa. Kyse on kuitenkin myös yrityksen juridisista mekanismeista ja työkaluista kuten sopimuksista, ja esimerkiksi siitä kattavatko työ- tai alihankintasopimukset riittävän hyvin oikeudet työntekijöiden tai alihankkijoiden keksintöihin. Kolmas ulottuvuus liittyy yrityksen organisatorisiin mekanismeihin, kuten ohjesääntöihin. Tutkimuksessa analysoidaan siten myös lain ulkopuolisia tekijöitä. Tämä väitöskirja tarjoaa perusteellisen kuvauksen oikeudellisista näkökohdista ja mahdollisista sudenkuopista kansainvälisen yrityksen rajat ylittävässä toiminnassa, prosessissa keksinnöstä patentiksi. Väitöskirjan tapausesimerkit tarjoavat arvokasta käytännön näkemystä potentiaalisten konfliktitilanteiden tunnistamiseen etukäteen ja ratkaisumalleja, jotka takaavat lainmukaisuuden. Lähestymistapa on siten proaktiivinen, sillä tavoite on tunnistaa ja ratkaista mahdolliset konflikti-tilanteet jo ennakolta, riitojen välttämiseksi tulevaisuudessa. Koska epäyhtenäiset työsuhde- ja patenttilainsäädännöt luovat yrityksille monimutkaisia compliance-velvoitteita, väitöskirjassa tutkitaan myös olisiko mahdollista luoda holistinen lähestymistapa, eri lakien noudattamiseksi, ensisijaisesti yrityksen omien ohjesääntöjen avulla, tai vaihtoehtoisesti tulevaisuudessa lakien harmonisoinnilla.